Synergistic anticancer effects of cisplatin and phenolic aglycones of the aerial part of Rumex dentatus L. in tongue squamous cell carcinoma: insights from network pharmacology and biological verification - Amany E. Ragab; Ghada M. Al-Ashmawy; Sherin R. El Afify; Ola A. El-Feky; Amera O. Ibrahim (BMC Complementary Medicine and Therapies)
Abstract Background Oral squamous cell carcinoma (OSCC) ranks as the sixth most common malignancy globally. Cisplatin is the standard chemotherapy for OSCC, but resistance often reduces its efficacy, necessitating new treatments with fewer side effects. Rumex dentatus L., from the Polygonaceae family, is known for its medicinal properties, but its anticancer potential has not been thoroughly explored. This study aimed to investigate the synergy between cisplatin and an extract from the aerial parts of R. dentatus L. in treating tongue carcinoma (HNO97) in vitro, using network pharmacology, biological verification, and phytochemical analysis. Methods The study included UPLC-ESI–MS/MS analysis, cytotoxicity assays, cell cycle analysis, apoptosis assessment, and RT-qPCR for gene expression of Bcl2, p53, and ATG7. Potential targets were identified, and mechanisms of action were examined through online databases and enrichment analyses. Results The R. dentatus L. extract contained 14 phenolic aglycons. Combining cisplatin and R. dentatus L. was more effective in inhibiting proliferation, inducing cell cycle arrest and apoptosis, and reducing autophagy in HNO97 cells than cisplatin alone. KEGG analysis indicated that the drug combination might work through pathways like PI3K-Akt signaling, microRNAs in cancer, and EGFR tyrosine kinase inhibitor resistance. Conclusions Combining cisplatin with R. dentatus L. may be a promising approach for treating tongue carcinoma by affecting multiple pathways, providing a new perspective for developing more effective treatments for OSCC.